Disclosure of Origin pada Pengakuan dan Publikasi Traditional Knowledge dalam Upaya Perlindungan Hukum - Endang Purwaningsih (Jurnal Hukum IUS QUIA IUSTUM, 2014)
The precise formulation of disclosure of origin as an attempt of international publication and recognition still faces big challenges. In addition to comprehending the philosophical values contained in the traditional knowledge, the evidence of historical originality of the traditional knowledge must be presented. The objectives of this research were to build the community empowerment model and legal awareness of promoting and protecting Indonesian traditional knowledge (first year) and to suggest a form of legal protection as well as national and international publications of disclosure of origin of Indonesian traditional knowledge (second year). The research method used was normative using sociological approach. Based on the research result, it was concluded that to precisely formulate the disclosure of origin, the Indigenous community must be a proactive subject as well as an agent to promote and protect. The legal protection for traditional knowledge could be realized by accommodating the traditional knowledge into the intellectual rights as a geographical indication and international recognition for the indigenous community communal ownership of the traditional knowledge since the developed countries tended to see it as a common heritage of mankind.